Beyond Profit: Institutional Entrepreneurship and Social Value Creation in Village-Owned Enterprises - Desti Fitriani; Amirul Shah Md. Shahbudin (Politeknik Siber Cerdika Internasional, 2026)
Background: The sustainability of Village-Owned Enterprises (BUMDes) remains a challenge, with many still dependent on government support. Previous studies have focused mainly on success and failure factors, while limited attention has been given to how sustainable BUMDes develop over time. Objective: Drawing on the institutional entrepreneurship perspective, this study examines how a village head initiated organizational transformation and how such transformation contributed to the sustainability of a BUMDes in Indonesia. Methods: This qualitative single-case study examined a BUMDes in a rural tourism destination in eastern Indonesia, selected for its financial growth and community programmes. Data were collected through interviews with five key informants, field observations, and document analysis, then analysed thematically through coding, theme development, and source triangulation. Results: The findings reveal that organizational transformation began with the reframing of the BUMDes’ purpose, followed by the mobilization of community resources and the reconfiguration of governance practices that supported organizational growth. More importantly, the study finds that social value creation served as a critical mechanism linking institutional entrepreneurship and organizational sustainability. Through expanding financial inclusion, creating employment opportunities, supporting local entrepreneurship, and implementing community welfare initiatives, the transformed BUMDes generated benefits that strengthened community support and sustained organizational development over time. Conclusion: This study contributes to the literature by extending institutional entrepreneurship research beyond organizational change and highlighting the role of social value creation in sustaining community-based enterprises. The findings also provide practical insights for policymakers and village leaders seeking to strengthen the long-term sustainability of village enterprises.